2003
DOI: 10.1037/0097-7403.29.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Temporally graded, context-specific retrograde amnesia and its alleviation by context preexposure: Effects of postconditioning exposures to morphine in the rat.

Abstract: Five experiments studied retrograde impairments in Pavlovian fear conditioning following prolonged exposure to the opioid receptor agonist morphine. Injections of morphine commencing 1-7 days but not 14 days after conditioning produced amnesia for that conditioning episode. This amnesia was (a) selective such that morphine impaired freezing to the conditioning context but not to the auditory conditioned stimulus, (b) independent of the interval between the last injection of morphine and test, and (c) accompani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Rats that have had an adrenalectomy, or hippocampal lesions, or that experience post-conditioning social isolation stress, morphine injections or bacterial lipopolysaccharide-induced inflammation show reduced CX- but not CS-fear. However, pre-exposing the rats to the context prior to conditioning can prevent these effects [3537,51,52]. Similarly, rats that have had long periods of time to explore the context prior to the shock (say, 120 s) show greater CX-fear conditioning than rats that are shocked shortly after being placed in the context (<27 s).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats that have had an adrenalectomy, or hippocampal lesions, or that experience post-conditioning social isolation stress, morphine injections or bacterial lipopolysaccharide-induced inflammation show reduced CX- but not CS-fear. However, pre-exposing the rats to the context prior to conditioning can prevent these effects [3537,51,52]. Similarly, rats that have had long periods of time to explore the context prior to the shock (say, 120 s) show greater CX-fear conditioning than rats that are shocked shortly after being placed in the context (<27 s).…”
Section: Discussionmentioning
confidence: 99%
“…Immediate post-conditioning injection of morphine [34], bacterial lipopolysaccharides [37] or live Escherischia coli [74], intracerebral infusions with proinflammatory cytokines [56] all specifically reduce context fear conditioning. In addition, context conditioning can also be reduced by experience with psychological stressors, such as social isolation, after conditioning [36] or by the chronic administration of opioids beginning days after conditioning [35]. …”
Section: Discussionmentioning
confidence: 99%
“…The endogenous opioid system may be involved in erasure of conditioned fear during extinction in P17 rats because there is evidence showing that the activation of opioid system disrupts consolidation of memory in adult rats. For example, postconditioning injections of opioid receptor agonists disrupt long-term memory (e.g., Rudy et al 1999;McNally and Westbrook 2003b). Therefore, increased opioid neurotransmission triggered by extinction training may cause some unlearning of the fear memory.…”
Section: Extinction Of Conditioned Fear In the Developing Ratmentioning
confidence: 99%
“…However, as neither NMDA or GABA seem to be involved in extinction in PND 16 rats (present results; Kim and Richardson 2007a), one potential mechanism for extinction in young rats is the endogenous opioid system. This neurotransmitter system has been found to regulate fear conditioning (McNally and Westbrook 2003) and extinction (McNally et al 2004) in adult rats. Moreover, the opioid system is a likely mechanism for mediating extinction in young rats, as it is active from birth (Blass et al 1991) and has been found to modulate memory in infant rats (Weber et al 2006).…”
Section: Org Downloaded Frommentioning
confidence: 99%